Empowering the food sector: A cooperative-based business partnership model at Al-Ittifaq Islamic Boarding School, Bandung - Rahman, Dwinda; Baga, Lukman Mohammad; Asikin , Zenal (Universitas Negeri Surabaya, 2025)
Farmer institutions have been unable to improve farmer production and welfare. Modern cooperatives are increasingly recognized for their good impact on farmers' well-being. This study seeks to identify critical success criteria for modern cooperatives, examine the performance of the Al Ittifaq Islamic Boarding School Cooperative (Kopontren), and investigate the responsibilities of stakeholders in their partnership value chain. This study also looks at the influence of these partnerships on farmer well-being and proposes an inclusive, sustainable food sector partnership model based on cooperatives. Data were acquired using qualitative descriptive methods, including narrative literature reviews, benchmarking, and in-depth interviews. The value chain analysis identified four major pillars of modern cooperatives: governance, economy, social, and environmental. Al Ittifaq Kopontren received a checklist rating of 0.66, indicating that it is good. Farmer incomes increased by 6-55% in 2023 compared to 2022, demonstrating the effectiveness of cooperative business partnerships in raising revenue. Future success necessitates the implementation of an inclusive, long-term partnership model involving strong institutions, research bodies, sustainable standards, and export-oriented and downstream product development.